P187 Correlation between the Lemann Index and the Inflammatory Bowel Disease-Disability Index in Crohn's disease. (16th January 2018) - Farré, C; Azahaf, M; Nachury, M; Branche, J; Gérard, R; Wils, P; Desreumaux, P; Ernst, O; Pariente, B
Abstract: Background: Crohn's disease (CD) is a chronic progressive destructive disease resulting in cumulative structural bowel damage, which may predict long-term disability. The Lemann Index (LI) has been developed to measure CD-related bowel damage, including surgical resection and The presence of stricturing and penetrating lesions; it could range from 0 to 140. The Inflammatory Bowel Disease-Disability Index (IBD-DI) has recently been validated to assess disability in a patient with IBD; it could range from 0 to 100. The aim of the study was to measure bowel damage by using the LI and disability by using the IBD-DI in a cohort of CD patients and to evaluate the correlation between the two indices. Methods: We performed a prospective study in the tertiary referral centre in Lille, from September 2016 to November 2016, including all consecutive CD outpatients. Bowel damage was assessed by the LI calculated according to the published protocol and disability by the IBD-DI questionnaire. Factors associated with LI and IBD-DI levels were identified by a median comparison test or means of bivariate analyses of variance. The correlation between the two indices was determined by a Spearman correlation test. Results: 130 CD patients were consecutively included. The mean of LI was 11.9 ± 14.1 and ranged from 0 to 72.5. The LI significantly increased with disease duration: median value of 0.9 (IQR, 0.3–2.2) for disease duration < 2 years, 1.6 (IQR, 0.3–10.8) for disease duration ≥2 and <10 years and 16.5 (IQR, 9.1–23.4) for disease duration ≥10 years. Anal location and exposition to anti TNF were associated with higher LI levels ( p < 0.005). Among patients exposed to anti TNF, the LI was lower in patients who were exposed in the first two years of the disease ( p = 0.015). The others factors associated with bowel damage were: previous intestinal resection, clinical and biological disease activity and exposition to immunosuppressants ( p < 0.005). The mean of IBD-DI was 28.8 ± 6.3 and ranged from 0 to 71. The factors associated with disability were: female gender, anal location, extradigestive manifestations, clinical and biological disease activity and exposition to anti TNF (p < 0.005). No significant correlation was found between LI and IBD-DI (ρ = 0.12; CI 95% −0.05–0.29; p = 0.15). Only a correlation between the anus LI and the IBD-DI was observed: ρ = 0.20 (CI 95% 0.003 −0.36), ( p = 0.02). Conclusions: Bowel damage but not disability increased with disease duration. Importantly, early introduction of anti TNF treatment prevented bowel damage progression. CD anal location was associated with high levels of LI and IBD-DI underlying the necessity to introduce early and intensive treatments in this CD population. No correlation was observed between the LI and the IBD-DI.